How Traditional Balinese Houses Can Adjust and Cater for International Tourist in the Canggu Area, Bali Indonesia? - Putu Suda Nurjani, Ni; Ketut Acwin Dwijendra, Ngakan (International Journal of Psychosocial Rehabilitation, 2020)
Bali has a unique architectural value. When tourism enters as a new culture, Balinese people need adjustments to the culture brought by tourists. Differences in tradition and culture in each Regency in Bali are the biggest obstacle for the government to make basic rules for housing. The height limit of a vertical building must not exceed the height of a coconut tree. This rule is the main obstacle to the development of high-rise buildings in Bali. This research is a case study that originates from many homestay phenomena which were raised as a trend of mass media coverage in Bali. Period of housing development is obtained through interviews with homeowners and tourists. Results of this study indicate that the ritual zone cannot be lost. The Canggu community did several things to maintain their residential units. First is adding space to existing buildings and making a combination in two or more occupant-owned buildings so that more rooms are available for commercial functions without sacrificing the ritual zone.